Pengembangan E-Modul Perkuliahan Tematik Terpadu Menggunakan Pendekatan Pembelajaran Aktif Mikir dan Project Based Learning Pada Program Studi Pendidikan Dasar Sumatera Selatan Indonesia - Ilham Arya Susanto; Amirul Mukminin Al Anwari; Muhaiminah Jalal (Departement of Mathematics Education, 2023)
This research aims to develop and produce a teaching material product in the form of an E-Module in Integrated Thematic Courses Using the MIKiR Active Learning Approach and Project Based Learning (PJBL) in the Basic Education Study Program which can be used effectively, easy to learn, simple and of course flexible for various circumstances. In addition, the developed E-Module can be used for a variety of learning approaches both synchronously and asynchronously so that it is able to accommodate lectures that are carried out in online and offline modes and also in Blended Learning mode. The development method used in the development of this E-Module is the Borg and Gall research and development method. While the expected results of the research are the birth of an integrated thematic Learning Lecture E-Module which consists of 7 constituent components namely titles, study guides, basic competencies or subject matter, supporting information (Additional Information, Supporting Videos in the form of links and QR Codes), exercises, tasks or work steps, and assessment. This e-module is validated by 3 validators who are experts in their fields. The validity of the product is based on the expert assessment of Thematic Learning conducted by Dr. Husni Mubarak, M.Pd.I with a score of 91.33% with the